Amputasi Ekstremitas Atas Akibat Luka Bakar Listrik : Laporan Kasus - Rahadi Arie Hartoko; Andi Amirah Shaleha Junaedi (Alami Journal (Alauddin Islamic Medical) Journal, 2023)
Amputation is a surgery that involves removing part or all of a limb or some abnormal growths from the body. The prevalence of amputations was approximately 1.6 million in 2005 in the United States and will double to 3.6 million in 2050. The main cause of upper extremity amputation is trauma, which is around 80%, especially in young adults with an incidence of amputation due to electrical burn injuries of around 2% (mainly transradial and transhumeral). The effects of an electric current depend on the type of current, voltage, tissue resistance, current strength, the path the current takes through the body, duration of contact, and individual susceptibility. Individuals undergoing upper extremity amputations need comprehensive rehabilitation by physiatrists, physiotherapists, occupational therapists, prosthetists, and psychologists. An appropriate rehabilitation program and a comfortable prosthesis (including maintenance of limb length) aim at prosthesis reconstruction. In addition to rehabilitation programs, appropriate amputation techniques can also facilitate individuals in the functional recovery process.